Liver elastography: clinical use and interpretation - Mueller, Sebastian (Springer eBook Collection, 2020)
Measurement of Liver stiffness – History, techniques, performance -- Transient elastography -- Sampling error -- ARFI and other US-based techniques -- MRE -- Animal studies -- Take home message -- Liver stiffness and its association with fibrosis -- Fibrosis Histology -- Disease etiology -- Take home message -- Important clinical confounders of LS -- CVP heart failure -- Arterial pressure -- Portal pressure -- Cholestasis -- Hydrostatic pressure -- Outflow inflow concept -- Nutrition and alcohol consumption -- position -- Histology correlates ballooning steatosis inflammation -- Genes Rausch -- Else amyloidosis, mastocytosis -- Take home message -- LS and important clinical endpoints -- HCC -- Portal hypertension, bleeding -- Survival -- Disease specific aspects -- LTX -- Hepatic decompensation -- Take home message -- How to use LS in clinical practice: State of the art 2019 -- Standard procedure position, technique, fasting -- Dissection from inflammation: Intervention and inflammation-adapted -- Disease specific algorithms: portal vs lobular vs cholestatic disease -- LS in combinations with spleen stiffness: portal hypertension and bleeding -- Spleen stiffness, techniques, spleen size -- Localization of hepatic disease: lobular, portal versus extrahepatic -- Comparison of various techniques -- Screening of populations -- Combination with serum markers -- Sparing of biopsies -- Take home message -- Future applications of LS -- Cardiololgy cardiac cirrhosis -- Intensive care unit mortality CVP -- Nephrology water retention -- Hematology -- LTX setting waiting list -- Screening in addiction medicine -- Pregnancy -- Therapeutic monitoring of portal pressure lowering drugs -- Other organs -- Specific interpretation in clinical context -- LS and hepatic vs non-hepatic ascites Ascites -- LS changes in cirrhotics -- Mechanic cholestasis -- Clinical cases -- CAP -- Steatosis techniques -- CAP performance -- Genetics -- Molecular insights based on LS -- Pressure hypothesis of liver fibrosis -- Stiffness in vitro -- Extracellular matrix and stiffness Matrix -- Future directions and open questions -- Molecular basics of LS -- Directions of future studies -- Future diagnostic algorithms.